2012
DOI: 10.4103/0019-5413.96390
|View full text |Cite
|
Sign up to set email alerts
|

MRI and ultrasonography in Morton’s neuroma: Diagnostic accuracy and correlation

Abstract: Background:The diagnosis of Morton's neuroma is based primarily on clinical findings. Ultrasonography (US) and magnetic resonance image (MRI) studies are considered complementary diagnostic techniques. The aim of this study was to establish the correlation and sensitivity of both techniques used to diagnose Morton's neuroma.Materials and Methods:Thirty seven patients (43 intermetatarsal spaces) with Morton's neuroma operated were retrospectively reviewed. In all cases MRI or ultrasound was performed to complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
1
20
0
7
Order By: Relevance
“…Besides the information regarding size and location, it provides more information about the nature of the lesion and surrounding changes, 12,13,26 and is able to distinguish the lesion from other soft-tissue masses with high signal intensity, such as bursae, schwannomas, and neoplasms. 2,27 Bencardino et al 19 reported that MRI had a sensitivity of 100% and a specificity of 68% in the investigation of Morton's neuroma, whereas Sharp et al 12 reported 86% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the information regarding size and location, it provides more information about the nature of the lesion and surrounding changes, 12,13,26 and is able to distinguish the lesion from other soft-tissue masses with high signal intensity, such as bursae, schwannomas, and neoplasms. 2,27 Bencardino et al 19 reported that MRI had a sensitivity of 100% and a specificity of 68% in the investigation of Morton's neuroma, whereas Sharp et al 12 reported 86% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16 Biasca et al 28 found that in contrast to the clinical findings, preoperative localization and diagnosis of Morton's neuroma was better achieved with MRI. 28 TorresClaramunt et al 13 came to the conclusion that MRI had a higher sensitivity than ultrasound and should be considered the technique of choice in some cases. The results of the present study support the former opinion, because ultrasound has a similar sensitivity, lower negative likelihood ratio, and higher specificity and positive likelihood ratio than MRI.…”
Section: Discussionmentioning
confidence: 99%
“…US sensitivity has been reported to be 56.5% to 100% in published studies (4,7,29,(32)(33)(34)(35). Likewise, the mean size of interdigital neuromas has been reported to vary from 4.9 to 7.4 mm (3,4,11,33,35,36).…”
Section: Discussionmentioning
confidence: 98%
“…The fact that none of our patients required neurectomy leads us to seriously question the existence of this condition as initially described. Numerous authors have noted the inaccuracy between the various diagnostic methods available for Morton's Neuroma [10,11]. These inaccuracies can result in illadvised and unnecessary treatment and even surgical interventions.…”
Section: Discussionmentioning
confidence: 99%